Sosioantropologi Pendidikan Islam: Mengintegrasikan Perspektif Sosial, Budaya, dan Antropologi - Adiyono, Adiyono; Nurohman, Dede; Harun, Makmur (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2024)
This study aims to examine the Islamic education system through a multidisciplinary perspective that integrates social, cultural, and anthropological aspects. The method used is a systematic literature review utilizing the ERIC, Crossref, Science Direct, JSTOR, ProQuest, and Google Scholar databases. The selection process, data extraction, and analysis were conducted systematically to ensure reproducibility and transparency. The results showed: 1) A multidisciplinary approach is essential in understanding the complexity of the Islamic education system; 2) Social, cultural, and historical factors have a profound impact on the philosophy and practice of Islamic education; 3) Anthropological perspectives are instrumental in understanding the influence of religious values and traditions on educational experiences; 4) This integrated approach has significant implications for educators, practitioners and policy makers in the field of Islamic education. The study concludes that the integration of social, cultural and anthropological perspectives provides a more comprehensive understanding of Islamic education. The implication is that a holistic approach is needed in curriculum development, teacher training and Islamic education policy. The study also identifies gaps in the literature and suggests directions for future empirical research.